Stimulation of Male Voice during Pregnancy Results in Higher Expression of Brain Derived Neurotrophic Factor in Cerebellum of Newborn Rattus norvegicus - Nurvy Alief Aidillah; Hermanto Tri Joewono; Widjiati (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Recent studies in the field of Fertomaternal Medicine show that stimulation in the uteruscan support brain growth and development. If in previous studies stimulation using several types of music,this study uses human voice which aims to analyze the effect of stimulation of male and female voices ondifferences in the expression of Brain Derived Neutrotrophic Factor (BDNF) in cerebellum of newbornRattus norvegicus. Methods: This type of research is true experimental with post test only control groupdesign. Rattus norvegicus was given stimulation of men voice and women voice on 6th day until 17th dayof pregnancy. The expression of BDNF was examined using immunohistochemistry. Results: The mean ±standard deviation of the expression of BDNF in the cerebellum is 4.20 ± 1.75 (without stimulation), 6.04± 1.58 (male voice stimulation), and 5.60 ± 2.43 (female voice stimulation). The results of statistical testsshow that there is a significant difference on BDNF expression between the control group and the groupstimulated with male voice with a significance value <0.05 of 0.045 Conclusion: Giving stimulation usingthe male voice during pregnancy shows a significant increase in the expression of BDNF in cerebellum ofnewborn Rattus norvegicus.